Nanotechnology tools for the study of RNA - Yoshizawa, Satoko (Progress in molecular biology and translational science, 2016)
This volume of 'Progress in Molecular Biology and Translational Science' introduces emerging strategies of studying RNA structure and function using nanotechnological tools. The volume aims to provide the readers with a novel view and give them opportunities to think about how to incorporate the new technologies into their own research.